2005
DOI: 10.1074/jbc.m414477200
|View full text |Cite
|
Sign up to set email alerts
|

βIII-Tubulin Induces Paclitaxel Resistance in Association with Reduced Effects on Microtubule Dynamic Instability

Abstract: The development of resistance to paclitaxel in tumors is one of the most significant obstacles to successful therapy. Overexpression of the ␤III-tubulin isotype has been associated with paclitaxel resistance in a number of cancer cell lines and in tumors, but the mechanism of resistance has remained unclear. Paclitaxel inhibits cancer cell proliferation by binding to the ␤-subunit of tubulin in microtubules and suppressing microtubule dynamic instability, leading to mitotic arrest and cell death. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
180
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 37 publications
15
180
0
Order By: Relevance
“…In addition, too high expression of class III b-tubulin in cells can be toxic, further complicating this methodology (Hari et al, 2003). To negate this problem Hari et al (2003) inducibly overexpressed class III b-tubulin in CHO cells, this decreased the paclitaxel suppression of microtubule dynamics and caused a limited resistance to paclitaxel (Kamath et al, 2005). Recently, cervical carcinoma HeLa cells were stably transfected with class III b-tubulin and were used to test taccalonolides, which were shown not to be susceptible to class III b-tubulin resistance (Risinger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, too high expression of class III b-tubulin in cells can be toxic, further complicating this methodology (Hari et al, 2003). To negate this problem Hari et al (2003) inducibly overexpressed class III b-tubulin in CHO cells, this decreased the paclitaxel suppression of microtubule dynamics and caused a limited resistance to paclitaxel (Kamath et al, 2005). Recently, cervical carcinoma HeLa cells were stably transfected with class III b-tubulin and were used to test taccalonolides, which were shown not to be susceptible to class III b-tubulin resistance (Risinger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the structure of the loop of the class III b-tubulin is altered by the substitution of Ser 277 with Arg and thus, prevents a stable paclitaxel binding . It has been shown that Class III b-tubulin also generates more dynamic microtubules and counteracts proassembling activity of taxanes at the plus ends of microtubules (Kamath et al, 2005), thereby making microtubules more resistant to the stabilisation of microtubule dynamics operated by taxanes (Hari et al, 2003;Kamath et al, 2005;Gan et al, 2007). In contrast, STX140, STX243, 2-MeOE2, ENMD1198 and colchicine are structurally different to paclitaxel; they bind to the colchicine site and they have a conformation, which may allow the formation of a stable complex with class III b-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for augmenting paclitaxel sensitivity is due to blocking one or more effects of TXA 2 . One of the major mechanisms for tumors to develop paclitaxel resistance is the elevation of b-III tubulin (Kamath et al, 2005). Both pharmacological and molecular inhibition of TXA 2 signaling resulted in reduction of b-III tubulin levels (Figures 2b and 4d), associated with increased sensitivity to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules consisting of the βIII-tubulin isotype have altered assembly properties, requiring a larger critical mass of tubulin for assembly, and polymerizing at a slower rate than other isotypes (16). In vitro, the overexpression of βIII tubulin results in increased resistance to taxane and vinorelbine (17,18). Elevated expression of βIII tubulin has also been correlated with clinical resistance to taxanes in a number of human cancers (19).…”
Section: Resistancementioning
confidence: 99%